2023
DOI: 10.1111/nmo.14624
|View full text |Cite
|
Sign up to set email alerts
|

Ineffective esophageal motility: The impact of change of criteria in Chicago Classification version 4.0 on predicting outcome after magnetic sphincter augmentation

Abstract: BackgroundThe most recent update of the Chicago Classification (CCv4.0) attempts to provide a more clinically relevant definition for ineffective esophageal motility (IEM). The impact of this new definition on predicting outcome after antireflux surgery is unknown. The aim of this study was to compare utility of IEM diagnosis based on CCv4.0 to CCv3.0 in predicting surgical outcome after magnetic sphincter augmentation (MSA) and to assess any additional parameters that hold value in future definitions.MethodsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…12 Another group found that IEM is poorly predictive of dysphagia after placement of a magnetic sphincter augmentation device, even when applying the more stringent criteria of Chicago Classification v4.0. 13…”
mentioning
confidence: 99%
“…12 Another group found that IEM is poorly predictive of dysphagia after placement of a magnetic sphincter augmentation device, even when applying the more stringent criteria of Chicago Classification v4.0. 13…”
mentioning
confidence: 99%